2017
DOI: 10.3389/fnhum.2017.00204
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Proactive and Reactive Motor Inhibition

Abstract: Proactive motor inhibition refers to endogenous preparatory mechanisms facilitating action inhibition, whereas reactive motor inhibition is considered to be a sudden stopping process triggered by external signals. Previous studies were inconclusive about the temporal dynamics of involved neurocognitive processes during proactive and reactive motor control. Using electroencephalography (EEG), we investigated the time-course of proactive and reactive inhibition, measuring event-related oscillations and event-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 68 publications
7
54
3
Order By: Relevance
“…Bereitschaftspotential (BP) ( 14 ) is the early subcomponent of MRCPs and is believed to be generated by the supplementary motor area (SMA) ( 15 ), motor cortex, and cingulate gyrus ( 14 , 16 ) and represents the motor preparation stage of movement. In addition to BP, a contingent negative variation (CNV) was reported to present in movement preparation stage ( 17 , 18 ) and reflects motor expectancy and preparation. The late subcomponent, the motor potential (MP), has been proposed to be generated from the underlying motor cortex and partly due to afferents excited by the movement ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bereitschaftspotential (BP) ( 14 ) is the early subcomponent of MRCPs and is believed to be generated by the supplementary motor area (SMA) ( 15 ), motor cortex, and cingulate gyrus ( 14 , 16 ) and represents the motor preparation stage of movement. In addition to BP, a contingent negative variation (CNV) was reported to present in movement preparation stage ( 17 , 18 ) and reflects motor expectancy and preparation. The late subcomponent, the motor potential (MP), has been proposed to be generated from the underlying motor cortex and partly due to afferents excited by the movement ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CNV is a gradient, negative slow ERP to cue stimuli (Walter, Cooper, Aldridge, McCallum, & Winter, ), which ceases at the presentation of a target stimulus (Bekker, Kenemans, & Verbaten, ). The neuronal source of both CNV and N1 is assumed to be located in the extrastriate cortex (Hillyard & Anllo‐Vento, ; Liebrand, Pein, Tzvi, & Kramer, ). N2 and P3 differ between go and nogo tasks, with a longer latency and more anterior topography for the nogo‐P3 and a more negatively and frontocentral topography for nogo N2 (Falkenstein, Hoormann, & Hohnsbein, ; Spronk, Jonkman, & Kemner, ).…”
Section: Introductionmentioning
confidence: 99%
“…The beta rebound is typically observed generally over sensorimotor areas after motor execution or motor imagery (Pfurtscheller et al, 2005;Pfurtscheller & Solis-Escalante, 2009) and it is believed to reflect an active recalibration process that takes place after a change in the state of the motor system (Pfurtscheller et al, 1996;Engel & Fries, 2010;Kilavik et al, 2013). Notably, the beta rebound over prefrontal and sensorimotor areas is considered a possible index of reactive control (Cooper et al, 2019;Liebrand et al, 2017). Accordingly, the presence of the beta rebound in our study only after a gait adjustment was required in order to step over an obstacle, provides a marker of the reactive process that needs to take place in order to restore the motor system to its previous state.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, wider evidence for reactive control mechanisms after movement. In particular, EEG studies have revealed post-movement increases of beta power (13-30 Hz), described as the beta rebound, as a marker of reactive control (Liebrand et al, 2017). Beta oscillatory activity over sensory motor regions is enhanced when the predictions of an incoming stimulus are violated (Arnal et al, 2011) and after forcibly interrupted movements (Alegre et al, 2008;Heinrichs-Graham et al, 2017), suggesting a mechanism that re-calibrates the motor system after a movement (Pfurtscheller et al, 1996;Engel & Fries, 2010;Kilavik et al, 2013).…”
Section: Introductionmentioning
confidence: 99%